2013
DOI: 10.3892/etm.2013.1342
|View full text |Cite
|
Sign up to set email alerts
|

Study of cell apoptosis in the hippocampus and thalamencephalon in a ventricular fluid impact model

Abstract: The aim of this study was to investigate the apoptosis of nerve cells in the hippocampal and thalamencephalon regions using a rabbit model of ventricular fluid impact. The results for the study demonstrated a variety of pathophysiological changes in the rabbit model, while changes in the hippocampal and thalamencephalon regions were observed under a light microscope following hematoxylin and eosin (H&E)/terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining. Among the mild, moderate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The programmed death cell or apoptotic process has a role in normal physiological processes such as morphogenesis, tissue remodelling, and resolution of the immune response ( 10 ). In addition, apoptotic changes in brain tissue samples have been found from animals ( 89 - 91 ) and humans ( 92 , 93 ) after a TBI. Besides, SIRS could appear after TBI ( 94 ) and this SIRS could activate the cellular death by apoptosis ( 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…The programmed death cell or apoptotic process has a role in normal physiological processes such as morphogenesis, tissue remodelling, and resolution of the immune response ( 10 ). In addition, apoptotic changes in brain tissue samples have been found from animals ( 89 - 91 ) and humans ( 92 , 93 ) after a TBI. Besides, SIRS could appear after TBI ( 94 ) and this SIRS could activate the cellular death by apoptosis ( 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…The rol of apoptosis in TBI remains unclear. However, there are data in animals [ 3 5 , 29 , 30 ] and human patients suggesting that apoptosis is present in TBI [ 6 , 7 ]. In a study with rats subjected to mild lateral fluid-percussion brain injury were found morphologic characteristics of apoptotic cell death in tissue homogenates [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study was performed a mild-moderate controlled cortical impact injury in mice and were found apoptotic changes in brain issues [ 4 ]. In a rabbit model study of ventricular fluid impact were found apoptotic changes in brain samples [ 5 ]. In TBI rat models were found a higher expression of pro-cell death genes (such as Bax) and a lower expression of anti-cell death genes (such as bcl-2 and bcl-xL) in brain tissue after TBI [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding cell apoptosis, the apoptosis of attached cells under fluid impact is a dynamic balance of continuous apoptosis and continuous detachment, and the cell populations maintain relatively stable proportions at different stages (20) Apoptotic cells, in particular those in the late stage, have a low adherence capacity and detach easily (21). In the present study, shaking led to apoptosis in the attached cells, which may result in the detachment of these cells from the flask wall and reduce the overall rate of apoptosis measured.…”
Section: Discussionmentioning
confidence: 99%